1985
DOI: 10.1159/000156201
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Values of Normal Bolivian Squirrel Monkeys (Saimiri sciureus): a Comparison between Wild-Caught and Laboratory-Bred Male Animals

Abstract: Complete and differential blood counts were conducted on 23 male squirrel monkeys (Saimiri sciureus) of Bolivian origin. The sample included 9 laboratory-bred and 14 wild-caught adult monkeys weighing between 600 and 1,500 g. The means of total white blood cell (WBC) counts, total hemoglobin and hematocrits of laboratory-bred animals were found to be significantly different from those of wild-caught monkeys (p < 0.01). Other hematologic parameters showed no significant differences between the two experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Comparison of normal hematologic parameters of animals in our colonies and data in the literature (Schultz 1961, Melville et al 1967, Robinson & Ziegler 1968, Stanley & Cramer 1968, Altshuler et al 1971, Ausman et al 1976, Beland et al 1979, Matsumoto et al 1980, Suzuki 1981, Kakoma et al 1985, 1987, Yoshida et al 1989, Buchl & Howard 1997 revealed discrepancies with significance levels of 0.1, 1 or 5%. The differences in the results may be accentuated by environmental factors and/or differences in the genetic make-up of our colony animals.…”
Section: Discussionmentioning
confidence: 55%
“…Comparison of normal hematologic parameters of animals in our colonies and data in the literature (Schultz 1961, Melville et al 1967, Robinson & Ziegler 1968, Stanley & Cramer 1968, Altshuler et al 1971, Ausman et al 1976, Beland et al 1979, Matsumoto et al 1980, Suzuki 1981, Kakoma et al 1985, 1987, Yoshida et al 1989, Buchl & Howard 1997 revealed discrepancies with significance levels of 0.1, 1 or 5%. The differences in the results may be accentuated by environmental factors and/or differences in the genetic make-up of our colony animals.…”
Section: Discussionmentioning
confidence: 55%
“…For instance, captive Brazilian howler monkeys kept 2-3 months in captivity ( Alouatta caraya ) exhibit higher cortisol levels compared to their wild counterparts (Sanchez-Sarmiento et al, 2015). Captive Squirrel monkeys ( Saimiri sciureus ) display significant variations in blood cell counts and haematological parameters compared to wild specimens (Kakoma et al, 1985). It is expected that after an initial period of arousal triggered by introduction to captivity, due to negative feedback a return to baseline would be observed (Parker-Fischer & Romero, 2019).…”
Section: Introductionmentioning
confidence: 99%